Alexander Williamson A Victorian chemist and the making of modern Japan - Inuzuka, Takaaki (UCL Press, 2021)
Alexander Williamson was professor of chemistry at UCL (1849-87) and a leading scientist of his time. He taught and cared for visiting Japanese students, thereby assisting them with their goal of modernising Japan. This short, accessible biography explores his contribution to nineteenth-century science as well as his lasting impact on Japanese society. In 1863 five students from the Chōshū clan, with a desperate desire to learn from the West, made their way to England. They were put in the care of Williamson and his wife. Their mission was to learn about cutting-edge Western technology, science, economics and politics. When they returned home they rapidly became leading figures in Japanese life at a particularly turbulent time, one of them serving as the country's first prime minister. Subsequently many other Japanese students followed in their footsteps and studied at UCL. The remarkable story of the part Williamson and UCL played in the modernisation of Japan is little known today. This biography will promote a deeper understanding of Williamson's scientific innovations and his legacy for Anglo-Japanese relations. An afterword briefly outlines the extraordinary careers of the pioneering students after they left Britain.